Stress Hyperglycemia in Patients With Acute Ischemic Stroke Due to Large Vessel Occlusion Undergoing Mechanical Thrombectomy - Merlino, Giovanni; Pez, Sara; Gigli, Gian Luigi; Sponza, Massimo; Lorenzut, Simone; Surcinelli, Andrea; Smeralda, Carmelo; Valente, Mariarosaria (Frontiers in Neurology, 2021)
Stress hyperglycemia may impair outcomes in patients with acute ischemic stroke (AIS) undergoing mechanical thrombectomy (MT). The glucose-to-glycated hemoglobin ratio (GAR) was used to measure stress hyperglycemia. Data from our database of consecutive patients admitted to the Udine University Hospital with AIS who were treated with MT between January 2015 and December 2020 were retrospectively analyzed. We included 204 patients in the study and stratified them into four groups according to the quartiles of GAR (Q1–Q4). The higher the GAR index, the more severe the stress hyperglycemia was considered. Patients with more severe stress hyperglycemia showed a higher prevalence of 3-month poor outcome (Q1, 53.1%; Q2, 40.4%; Q3, 63.5%; Q4, 82.4%; p = 0.001), 3-month mortality (Q1, 14.3%; Q2, 11.5%; Q3, 15.4%; Q4, 31.4%; p = 0.001), and symptomatic intracranial hemorrhage (Q1, 2%; Q2, 7.7%; Q3, 7.7%; Q4, 25.4%; p = 0.001). After controlling for several confounders, severe stress hyperglycemia remained a significant predictor of 3-month poor outcome (OR 4.52, 95% CI 1.4–14.62, p = 0.012), 3-month mortality (OR 3.55, 95% CI 1.02–12.29, p = 0.046), and symptomatic intracranial hemorrhage (OR 6.89, 95% CI 1.87–25.36, p = 0.004). In summary, stress hyperglycemia, as measured by the GAR index, is associated with a detrimental effect in patients with AIS undergoing MT.